Soil properties, minerological compositions and micromorphological features of red clays in Hungary - Fekete, József; Szendrei, Géza; Csibi, Melinda (JOURNAL OF LANDSCAPE ECOLOGY, 2005)
Former ideas on formations and properties as well as extent of red clays in Hungary are compiled in the introduction. The topographical data of the sites and the descriptions of the samples are given. Basic soil physical, -chemical, -mineralogical and micro morphological analyses of 17 samples from different regions of the country were performed. The analyses were carried out by the Hungarian standard methods. The micro morphological characteristics were interpreted as the features of swelling and shrinking, or those of illuviations, or those of precipitation of CaCO3 along the pores. Evaluating the data red clays investigated can be rank into different regions as follows: red soils of the Northern-Borsod karst region, red clays of Mátra Mountains, of its foothills and of upper course region of Zagyva River, red clays of the Northern periphery of the Great Hungarian Plain, red soils formed on Permian sandstones, red clays of the Szekszárd hilly region, red clays of the Mecsek-Villány Mountains.
Keywords: red clays; red soil; laterization; rubefication; micro morphological characteristics; swelling-shrinking; illuviation